Holliday junction–ZMM protein feedback enables meiotic crossover assurance - Adrian Henggeler; Lucija Orlić; Daniel Velikov; Joao Matos (Nature, 2025)
Abstract Holliday junctions (HJs) are branched four-way DNA structures that link recombining chromosomes during double-strand break repair 1 . Despite posing a risk to chromosome segregation, HJs accumulate during meiotic prophase I as intermediates in the process of crossing-over 2,3 . Whether HJs have additional regulatory functions remains unclear. Here we establish an experimental system in budding yeast that enables conditional nucleolytic resolution of HJs after the establishment of meiotic chromosome synapsis. We find that HJ resolution triggers complete disassembly of the synaptonemal complex without disrupting the axis–loop organization of chromosomes. Mechanistically, HJs mediate the continued association of ZMM proteins with recombination nodules that form at the axes interface of homologous chromosome pairs. ZMM proteins, in turn, promote polymerization of the synaptonemal complex while simultaneously protecting HJs from processing by non-crossover pathways. Thus, reciprocal feedback between ZMMs, which stabilize HJs, and HJs, which retain ZMM proteins at future crossover sites, maintains chromosome synapsis until HJ-resolving enzymes are activated during exit from prophase I. Notably, by polymerizing and maintaining the synaptonemal complex structure, the HJ–ZMM interplay suppresses de novo double-strand break formation and recombination reinitiation. In doing so, this interplay suppresses the DNA damage response, enabling meiotic progression without unrepaired breaks and supporting crossover assurance.